ANALISIS HUBUNGAN TINGKAT KONTRIBUSI DAN PERAN ISTRI NELAYAN TERHADAP EKONOMI KELUARGA DI PANTAI DEPOK KABUPATEN BANTUL - Putri, Meli Mahfiroh Karisma; Nurhayati, Atikah; Herawati, Titin; Maulina, Ine (Universitas Pattimura, 2024)
This research was conducted from November 27, 2023, to February 9, 2024, in five hamlets: Dusun Depok, Dusun Duwuran, Dusun Samiran, Dusun Bungkus, and Dusun Karang. The purpose of this research is to analyze the relationship between the role and contribution level of fishermen's wives in Depok Beach towards the family economy. The method used is a survey method utilizing Likert scale questionnaires and interviews. The highest contribution level is held by fishermen's wives who work as grocery store traders, amounting to 67%. Based on the research results, there is a significant relationship between the public role, domestic role, and contribution level of fishermen's wives in Depok Beach towards the family economy. Therefore, the role and contribution level of fishermen's wives in Depok Beach play an important role in improving the family economy